PEMBERDAYAAN FUNGSI MANAJEMEN REMAJA MASJID BAITUL AMAL PULAU RAJO INDERAPURA - Susyanti, Susyanti; Rimin, Rimin; Bustami, Bustami; Ikhlas, Nur (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
This research aims to analyze the main issues related to empowering youth management functions at Baitul Amal Rajo Island, Inderapura. The aim of this research is to understand the challenges teenagers face in managing time, resources and relationships with others, as well as to identify effective empowerment strategies to improve teenagers' managerial abilities. This research uses an Asset Based Community Development (ABCD) based approach, which is a consultative process to achieve the ability to inform the values of the younger generation as a community and local area. The results of this research show that teenagers in Baitul Amal Rajo Island Inderapura face challenges in managing time, resources, and relationships with others